MicroRNA networks regulated by all-trans retinoic acid and Lapatinib control the growth, survival and motility of breast cancer cells - Fisher, James Neil (Oncotarget, 2015)
SKBR3-cells, characterized by ERBB2/RARA co-amplification, represent a subgroup of HER2(+) breast-cancers sensitive to all-trans retinoic acid (ATRA) and Lapatinib. In this model, the two agents alone or in combination modulate the expression of 174 microRNAs (miRs). These miRs and predicted target-transcripts are organized in four interconnected modules (Module-1 to -4). Module-1 and Module-3 consist of ATRA/Lapatinib up-regulated and potentially anti-oncogenic miRs, while Module-2 contains ATRA/Lapatinib down-regulated and potentially pro-oncogenic miRs. Consistent with this, the expression levels of Module-1/-3 and Module-2 miRs are higher and lower, respectively, in normal mammary tissues relative to ductal-carcinoma-in-situ, invasive-ductal-carcinoma and metastases. This indicates associations between tumor-progression and the expression profiles of Module-1 to -3 miRs. Similar associations are observed with tumor proliferation-scores, staging, size and overall-survival using TCGA (The Cancer Genome Atlas) data. Forced expression of Module-1 miRs, (miR-29a-3p; miR-874-3p) inhibit SKBR3-cell growth and Module-3 miRs (miR-575; miR-1225-5p) reduce growth and motility. Module-2 miRs (miR-125a; miR-193; miR-210) increase SKBR3 cell growth, survival and motility. Some of these effects are of general significance, being replicated in other breast cancer cell lines representing the heterogeneity of this disease. Finally, our study demonstrates that HIPK2-kinase and the PLCXD1-phospholipase-C are novel targets of miR-193a-5p/miR-210-3p and miR-575/miR-1225-5p, respectively.